Implementation of Al-Qur'an Learning Using the Wafa Method in SD IT Insan Mulia Bambanglipuro Bantul Yogyakarta - Annisa Lutfiana (Educan : Jurnal Pendidikan Islam, 2023)
Every Muslim must learn the Qur'an; one way to do this is to read and memorize its passages. The Wafa method uses Hijaz tones to make memorizing the Qur'an entertaining, adaptable, and long-term memory-friendly. The 5P stages: Opening, Experience, Teaching, Assessment, and ClosinG make up the Wafa method. This study describes how the Wafa method of memorizing the Qur'an at SD IT Insan Mulia is used and its limitations. This study is conducted in the field and uses a qualitative descriptive strategy to gather data through observation, interviews, and recording. The four steps of the data analysis process used in this study are data reduction, data presentation, data validity testing, and conclusion. In this instance, the researcher described how the Wafa technique was used to teach the Al-Qur'an at SD IT Insan Mulia Bambanglipuro. According to the study's findings, recitation learning is implemented utilizing the Wafa method in five stages: the opening, the experience, the teaching, the assessment, and the close. Introduction, talaqqi, takrir, evaluation, and closing make up the Wafa method's application of tahfidz learning. Second, different children's levels of proficiency in completing Wafa volume books, a lack of Wafa-certified teachers, conditioning of the students, a shortage of Al-Qur'an teachers, the short length of Wafa lessons, the lack of cooperation between teachers and students' guardians, the absence of tahfidz teachers creating murojaah media, and varying levels of student interest are all barriers to learning the Qur'an using the Wafa method.